2013
DOI: 10.1016/j.apenergy.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of financial mechanisms in support to new pumped hydropower storage projects in Croatia

Abstract: h i g h l i g h t s" The most widespread storage in power systems is the pumped/reversible hydro storage. " The electricity market does not adequately rewarded all services that PHS provide to the electricity system. " The FIT-GO varies in the range of 42-265 €/MW h for an average capacity factor of 20%. a r t i c l e i n f o t r a c tThis paper analyses potential supporting schemes for pumped hydro storage (PHS) facilities in Croatia, which would guarantee recovery of the investment cost, with feed-in tariff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…The production from RES, characterized by variable temporal availability, unpredictable over time, can in fact efficiently meet energy needs if coupled with storage systems (mechanical, electrical, chemical, thermal, biological, etc. ): it follows that thanks to its energy performance and its environmental sustainability, the interest in hydrogen as energy carrier is growing today [9][10][11].…”
Section: The Transition To a New Energy Paradigmmentioning
confidence: 99%
“…The production from RES, characterized by variable temporal availability, unpredictable over time, can in fact efficiently meet energy needs if coupled with storage systems (mechanical, electrical, chemical, thermal, biological, etc. ): it follows that thanks to its energy performance and its environmental sustainability, the interest in hydrogen as energy carrier is growing today [9][10][11].…”
Section: The Transition To a New Energy Paradigmmentioning
confidence: 99%
“…where a, b are constants. It can be seen from Equations (7) to (11) when the operating power of the regenerative electric boilers is running under the mode of tracking the curtailed wind, it can consume more curtailed wind. After the energy storage system is added to the wind power heating system, it will track the curtailed wind more timely and accurately, improving the imbalance problem between the "source" and "load", reduce the adjusting numbers of the electrode rods, and prolong the service life of the regenerative electric boilers.…”
Section: Wind Power Heating Mechanism Using Energy Storage System To mentioning
confidence: 99%
“…A pumped storage power station is used to store the curtailed wind at night in the form of water energy, and deliver them to the grid when the load is in peak periods in the daytime, which has been widely used in many countries and regions. However, its construction period is too long [10][11][12]. Electric boilers can directly consume the curtailed wind for heating in low load periods to mitigate the heat pressure of the CHP units.…”
mentioning
confidence: 99%
“…In [8], it was determined that it is not possible to create a return on investment if the electricity price does not increase more than the inflation for battery storage for houses, considering the subsidy system, the electricity price, and the purchase cost of a PV installation and a battery system. In [9] an analysis of potential supporting schemes for pumped hydro storage facilities in Croatia concluded that a clear regulatory framework is necessary (e.g., applying a feed-in tariff, which guarantees the payment of the capital cost and a reasonable rate of return). [10] proposed a model for the economic feasibility of CAES improves wind power integration and found that given the present conditions on the minute reserve market, no CAES power plant is economically feasible.…”
Section: Introductionmentioning
confidence: 99%